IMPLEMENTING CHARACTER EDUCATION THROUGH PROBLEM-BASED LEARNING IN SOCIOLOGY SUBJECTS FOR THE DEVELOPMENT OF SOCIAL CAPITAL - Arofah, Lumban (Vidya Karya Jurnal Kependidikan, 2015)
The era of globalization is supported by education as a major pillar in various aspects. Therefore, especially for developing countries, improving the quality of education is one way to equip its citizens in an effort to face the globalization era. However, it should be made aware that improving the quality of education should be aligned with a character that is owned by the nation, considering the character is part of the identity and culture of the nation. This article seeks to contribute in providing idea in the form of character education through problem-based learning model in sociology subjects for the creation of social capital started from school.